2019
DOI: 10.1103/physrevb.100.235142
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a metallic metastable phase induced by electrical current in Ca2RuO4

Abstract: A comprehensive study of the behavior of the Mott insulator Ca2RuO4 under electrical current drive is performed by combining two experimental probes: the macroscopic electrical transport and the microscopic X-Ray diffraction. The resistivity, ρ, vs electric current density, J, and temperature, T , ρ(J,T), resistivity map is drawn. In particular, the meta-stable state, induced between the insulating and the metallic thermodynamic states by current biasing Ca2RuO4 single crystals, is investigated. Such an analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 33 publications
(73 reference statements)
6
35
1
Order By: Relevance
“…Layered perovskite Ca2RuO4 (CRO) is one such material, where the metal-insulator transition is induced by currents or fields through electron redistributions in the 4d t2g orbitals. 9,10,[13][14][15][16] In CRO, novel electronic properties that do not appear in the thermally induced phases have been observed in the electrically induced phases, including strong diamagnetism under a high current density. 13 This indicates the particular importance of the electricity induced transitions of CRO because the electrically driven transitions in other materials generally induces only the same phases with the thermally driven transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Layered perovskite Ca2RuO4 (CRO) is one such material, where the metal-insulator transition is induced by currents or fields through electron redistributions in the 4d t2g orbitals. 9,10,[13][14][15][16] In CRO, novel electronic properties that do not appear in the thermally induced phases have been observed in the electrically induced phases, including strong diamagnetism under a high current density. 13 This indicates the particular importance of the electricity induced transitions of CRO because the electrically driven transitions in other materials generally induces only the same phases with the thermally driven transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, current density as a function of electric field is hysteretic which complicates the study of size effects carried out here. We have conducted electric field versus current density (E(J)-characteristic) and resistivity measurements as a function of temperature and found that the microscopic samples qualitatively show similar behavior as the mm-sized bulk samples 14 . Typical results from microscopic samples are summarized in Fig.…”
Section: Characterizing Microscopic Samplesmentioning
confidence: 99%
“…A prime example of this, is the family of ruthenates witch exhibits a rich and diverse phase diagram that includes Mott insulators 6,7 , unconventional superconductivity 8,9 , and magnetism 10,11 . The 4d electron Mott insulator Ca 2 RuO 4 6 (hereafter Ca214) has become the subject of intense research in recent years due to its intriguing electrical [12][13][14][15][16][17][18][19][20][21][22][23][24] and magnetic properties 25,26 . Specifically, at room temperature it undergoes a current-driven insulator to metal transition (IMT) which occurs at unusually low electric (E-)field or current density (J) thresholds (~40 V/cm or few A/cm 2 respectively) 27,28 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations